Requirement of the Nigerian indigenous fowl for protein and amino acids. - OLUYEMI, J. A.; LONGE, O.; SONGU, T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
A total of six hundred 28 weeks Old Nigerian indigenous hens were randomly alloted to 10 diets containing either 15 or 18% crude protein and varying levels of lysine and sulphur amino acids. Different dietary levels of fish meal and blood meal were used to achieve the above. Dietary protein level had no effect (P > 0.05) on egg production, egg quality, feed efficiency and mortality, while egg size was increased (P< .05) by amino acid profile. Egg production tended to. increase with better amino acid profile but both egg production (30.8 - 42.4%) and egg size (39.7 - 43.5g) appeared to be generally low. However, egg size and Haugh Unit were considerably improved (54.39%) and 77.48% respectively) in a second experiment using a dietary regime with 21% crude protein and the high of fish real and blood meal used in the first experiment.